Targeting the NAT10/NPM1 axis abrogates PD-L1 expression and improves the response to immune checkpoint blockade therapy - Ge Qin; Fan Bai; Huabin Hu; Jianwei Zhang; Weixiang Zhan; Zehua Wu; Jianxia Li; Yang Fu; Yanhong Deng (BMC, 2024)
Abstract Background PD-1/PD-L1 play a crucial role as immune checkpoint inhibitors in various types of cancer. Although our previous study revealed that NPM1 was a novel transcriptional regulator of PD-L1 and stimulated the transcription of PD-L1, the underlying regulatory mechanism remains incompletely characterized. Methods Various human cancer cell lines were used to validate the role of NPM1 in regulating the transcription of PD-L1. The acetyltransferase NAT10 was identified as a facilitator of NPM1 acetylation by coimmunoprecipitation and mass spectrometry. The potential application of combined NAT10 inhibitor and anti-CTLA4 treatment was evaluated by an animal model. Results We demonstrated that NPM1 enhanced the transcription of PD-L1 in various types of cancer, and the acetylation of NPM1 played a vital role in this process. In particular, NAT10 facilitated the acetylation of NPM1, leading to enhanced transcription and increased expression of PD-L1. Moreover, our findings demonstrated that Remodelin, a compound that inhibits NAT10, effectively reduced NPM1 acetylation, leading to a subsequent decrease in PD-L1 expression. In vivo experiments indicated that Remodelin combined with anti-CTLA-4 therapy had a superior therapeutic effect compared with either treatment alone. Ultimately, we verified that the expression of NAT10 exhibited a positive correlation with the expression of PD-L1 in various types of tumors, serving as an indicator of unfavorable prognosis. Conclusion This study suggests that the NAT10/NPM1 axis is a promising therapeutic target in malignant tumors.